2008
DOI: 10.1098/rspb.2008.0136
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of sex ratio adjustment in a pollinating fig wasp

Abstract: Sex ratio strategies in species subject to local mate competition (LMC), and in particular their fit to quantitative theoretical predictions, provide insight into constraints upon adaptation. Pollinating fig wasps are widely used in such studies because their ecology resembles theory assumptions, but the cues used by foundresses to assess potential LMC have not previously been determined. We show that Liporrhopalum tentacularis females (foundresses) use their clutch size as a cue. First, we make use of species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
105
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(112 citation statements)
references
References 34 publications
6
105
0
1
Order By: Relevance
“…K. tentacularis foundresses use their clutch size as a cue to assess potential local mate competition, producing mainly males at the beginning of their oviposition sequence (Moore et al 2005;Raja et al 2008a). As foundress number increases, the average numbers of eggs laid by each female declines, showing that there is competition for oviposition sites (Raja et al 2008a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…K. tentacularis foundresses use their clutch size as a cue to assess potential local mate competition, producing mainly males at the beginning of their oviposition sequence (Moore et al 2005;Raja et al 2008a). As foundress number increases, the average numbers of eggs laid by each female declines, showing that there is competition for oviposition sites (Raja et al 2008a).…”
Section: Methodsmentioning
confidence: 99%
“…With an increase in the number of foundresses contributing to a brood inside a fig, local mate competition is spread among offspring of more females and a less female-biased progeny sex ratio becomes optimal (Hamilton 1967;Raja et al 2008a). Empirical studies have confirmed that as more foundresses enter a fig there is often a reduction in the extent to which their combined broods are female biased, in line with theoretical predictions, but there is often considerable variation between figs: fig wasp sex ratios are not precise (Greeff and Compton 1996;Herre 1987;Raja et al 2008a).…”
mentioning
confidence: 99%
“…They lay their eggs inside galled ovules of the numerous tiny flowers that line the inside of the Ficus inflorescence-the fig [7]. PFW progeny sex ratios are female biased, but typically become less biased when increasing numbers of foundress females enter a fig [8]. Adult male PFW are shortlived and flightless.…”
Section: Introductionmentioning
confidence: 99%
“…When fig wasps and parasitoid wasps lay eggs in a patch, unfertilized eggs may be laid during the early duration of oviposition (Godfray 1994;Kjellberg et al 2005;Moore et al 2005;Raja et al 2008). Such a 'male-first strategy' facilitates the production of optimal sex ratios by female parasitoids.…”
mentioning
confidence: 99%
“…Such a 'male-first strategy' facilitates the production of optimal sex ratios by female parasitoids. If multifoundresses oviposit in a patch, there may be a reduction in clutch size per foundress because of limited oviposition sites in the patch (Moore et al 2005;Raja et al 2008). Higher proportion of male offspring means higher fitness to foundresses, because male offspring have the potential to mate with the female offspring of the other foundresses and the value of males increases (Hamilton 1967;Hu et al 2010;West 2009).…”
mentioning
confidence: 99%